2
$\begingroup$

I am trying to understand why the Euler-Mascheroni constant $\displaystyle \gamma = \lim_{n \rightarrow \infty} \left ( \sum_{k=1}^n \frac{1}{k} - \ln n \right )$ is equal to $1 - \displaystyle \int_{1}^{\infty} \frac{t-[t]}{t^2}\; \mathrm{d}t$ where $[t]$ is the floor function.

There has been an answered question here already:
Integral form for the euler-mascheroni gamma constant using floor function

However, there is one line I do not understand and will appreciate help on explaining why the following equality is true: $$ \lim_{m\rightarrow \infty} \sum_{n=1}^{m} (\ln (1 + \frac{1}{n})-\frac{1}{n+1})= 1 - \gamma $$

$\endgroup$
4
$\begingroup$

Note that

$$\ln \left(1+\frac{1}{n}\right) = \ln \frac{n+1}{n} = \ln (n+1) - \ln n.$$

Hence

$$\begin{align} \sum_{n=1}^m \left(\ln \left(1+\frac{1}{n}\right) - \frac{1}{n+1}\right) &= \sum_{n=1}^m (\ln (n+1) - \ln n) - \sum_{n=1}^m \frac{1}{n+1}\\ &= \underbrace{\ln (m+1) - \sum_{k=1}^{m+1} \frac{1}{k}}_{\to -\gamma} + 1. \end{align}$$

$\endgroup$
4
$\begingroup$

However, there is one line I do not understand and will appreciate help on explaining why the following equality is true: $$\lim_{m\to\infty} \sum_{n=1}^m \left( \ln \left(1 + \tfrac{1}{n}\right) - \frac{1}{n+1}\right) = 1-\gamma$$

Observe that $\ln \left(1 + \frac{1}{n}\right) = \ln (n+1) - \ln n \implies \displaystyle\sum_{n=1}^m \ln \left(1 + \frac{1}{n}\right) = \ln (m+1)$ (it telescopes).

Therefore $$\sum_{n=1}^m \left(\ln \left(1 + \tfrac{1}{n}\right) - \frac{1}{n+1}\right) = \ln (m+1) - \sum_{n=1}^{m+1} \frac{1}{n} + 1$$

and $$\ln (m+1) - \sum_{k=1}^{m+1} \frac{1}{n} \to -\gamma$$ as $m\to\infty$ by definition.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.